Relationship Between Body Mass Index and Health and Occupational Performance Among Law Enforcement Officers, Firefighters, and Military Personnel: A Systematic Review. (7th June 2021) - Sergi, Tina; Bode, Katherine; Hildebrand, Deana; Dawes, Jay; Joyce, Jill
Abstract: Objectives: The prevalence of overweight and obesity among tactical populations is estimated at 70–75%, which may negatively impact health and performance. Since the relationship between BMI and health and performance is not well studied in tactical populations, the purpose of this study was to systematically review available literature on the relationship between BMI and health and performance among law enforcement officers (LEO), firefighters, and military personnel. Methods: Literature searches were conducted in PubMed and SCOPUS using combinations of search terms: body mass index, health*, cardiovascular disease, heart disease, heart attack, myocardial infarction, heart failure, stroke, hypertension, cancer, diabetes, performance, physical fitness test*, physical training, fitness test*, injur*, law enforcement, police, trooper, firefighter, military, soldier, airmen, and sailor. Included studies used BMI as an adiposity assessment; involved cardiovascular disease (CVD), cancer, diabetes (T2DM), performance testing, and injuries among US LEOs, firefighters, or military personnel; and involved peer-reviewed primary research between 2000–2020. Review studies; studies on other tactical populations, retirees, and trainees; and studies using BMI as a covariate were excluded. Included articles were critically appraised using the Academy of Nutrition and Dietetics Quality Criteria Checklist. Results: Twenty-seven articles were included. Overall quality was neutral. Nine studies found BMI was positively associated with CVD risk factors. Studies involving BMI and cancer were lacking. One study found BMI was positively associated with T2DM risk. Five studies on occupational/physical performance and twelve studies on injury found a higher BMI was often indicative of decreased performance and increased risk of injury in general, but protective against stress fractures. Conclusions: Higher BMI was often associated with negative health and performance outcomes among tactical populations, especially when beyond the overweight classification. Public health practitioners should focus efforts on improving nutrition and physical activity to promote a healthy BMI among these individuals. Funding Sources: None.